Relationship between Customer Relation Management Performance and E-Banking Adoption : A Look at Malaysian Banking Industry - Samsudin, Wahab; Nor Azila, Mohd Noor; Juhary, Ali; Kamaruzaman, Jusoff (2009)
This study seeks to identify the relationship between CRM performance and e-banking adoption. CRM performance is the process of value creation which results into the customer behavior intention (retain, repurchase, positive word of mouth), customer satisfaction and loyalty towards the product/brand. Despite of the popular practice of CRM in various industries, and particularly in banking, there is still lack of empirical studies, investigating to what extent the CRM performance influences on e-banking adoption. Hypothesized relationships were tested using survey responses from a sample of 307 lecturers at three public universities located in the northern states of Malaysia. The results which were compared with earlier findings illustrated that CRM performance does offer a positive influence on e-banking adoption and implications for further research were also being discussed.